Learning Loss and Educational Inequalities in Europe: Mapping the Potential Consequences of the COVID-19 Crisis - Zsuzsa Blaskó; Patricia da Costa; Sylke V. Schnepf (Institute of Labor Economics (IZA), 2021)
It is widely discussed that the pandemic has impacted on educational inequalities across the world. However, in contrast to data on health or unemployment, data on education outcomes are not timely. Hence, we have extremely limited knowledge about the actual impact of the pandemic on learning outcomes at the national and the cross-national level. As it might take years to get new comparative evidence on the actual extent of the problem, this paper uses the latest large scale international student assessment data from before the pandemic, the Trends in International Mathematics and Science Study (TIMSS) 2019 and applies simple descriptive analysis, regressions and logical deductions to map potential consequences of the Covid-19 crisis across Europe. We obtain the relative trajectories of children's learning loss and its unequal distribution from information on home and school resources, the importance of these resources for learning outcomes and countries' school closure duration policies and compare Covid-19 related risk of learning loss between European countries. Results based on 4th graders' school achievements indicate that throughout Europe educational inequalities between and within countries are likely to increase substantially. Some European countries are highly likely to face already an education crisis.
Keywords: I24; 330; educational inequalities; COVID-19; Europe; learning loss